Mineral Phosphate Solubilization in Burkholderia tropica Involves an Inducible PQQ-Glucose Dehydrogenase - Bernabeu, Pamela Romina (2016)
Aims: The objective of this work was to provide knowledgement about the mechanism and regulation of the mineral phosphate solubilization in Burkholderia. tropica. To this end, the expression of the direct extracellular oxidative pathway in B. tropica was studied using different culture approaches.Study Design: Plate assays and batch cultures in flasks and bioreactor were carried out in this study with B. tropica Mto-293 like target organism. The experiments were achieved at least three times with two repetitions per time.Place and Duration of Study: Departamento de Química, Centro de Investigación y Desarrollo en Fermentaciones Industriales, UNLP, CCT-La Plata-CONICET, between November 2014-2015.Methodology: Qualitative plate assays with different Carbon sources were carried out for the evaluation of Mineral Phosphate Solubilization phenotype. Batch cultures in flasks were carried out with different Carbon, Phosphorus and Nitrogen sources to determine quantitatively soluble phosphorus, gluconic acid and other ketoacids in the supernatants, and also PQQ-linked glucose and gluconate dehydrogenase activities in whole cells. Cultures with some of the conditions mentioned before were carried out in bioreactor specifically to control pH.Results: This organism was able to produce significant amounts of gluconic acid via the expression of a PQQ-GDH and also showed a significant activity of GaDH. However, the direct oxidative pathway was only observed under conditions of Phosphorus starvation and/or Nitrogen fixation.Conclusion: The Mineral Phosphate Solubilization phenotype for B. tropica can be ascribed to the expression of the direct oxidative pathway which involves the expression of an active PQQ- linked glucose dehydrogenase. Nevertheless, this pathway is not expressed constitutively in this bacterium. Environmental conditions, like low P and N availability, led to an active extracellular glucose oxidation. Therefore, mineral phosphate solubilization in B. tropica involves an inducible pyrroloquinoline quinone-linked glucose dehydrogenase. These findings may contribute to the use of this bacterium as plant growth promoting bacteria reducing the dependence on chemical fertilizer.